Environmental Impact Assessment: Integrated Evaluation of Bridge Construction Project in Bangladesh - Hasan, Irteja; Shaha, Milton; Shafiqul Islam, Md; Sirajul Islam, Md; Solayman, Md; Hossen, Miraz; Humayun Kabir, Md (International Journal of Advanced Geosciences, 2018)
Environmental Impact Assessment (EIA) may provide a mechanism for executing sustainable development and it is also becoming a very significance revision before authorizing of any project plan. EIA helps to decision making process whether the project is beneficial or harmful effects for the environment. Both on site and off site environmental impacts can be reduced through undertaking EIA for any bridge construction activities. This paper mainly concentrates on to find out potential environmental impact during the construction, operation and maintenance phase of the project using different matrix method. It also finds out the effective mitigation measures of the adverse impacts that will be helpful for the surrounding environment. Primary data were collected from field survey, focus group discussion. Most of the impacts and other consequences are identified based on public perception and the interview of the key personnel’s. Secondary data were also collected for conducting the research. The study found that the bridge is connecting three regions (Bauphal, Patuakhali and Barisal) and it will be a great achievement for the local coastal community. This new bridge project will not only increase the communication facilities but also other facilities such as economic flow, medical facilities etc. The EIA study founds some major negative Impacts such as loss of land and resettlement, loss of aquatic habitat, loss of local trees varieties, loss of agricultural lands, loss of vegetation, potential impact on ecological resources, impact on fish migration etc. But analyzing the overall impact of the environment, the EIA study found that that the possible negative impact is not so high and the project can be implemented. Different environmental management plans are suggested for reducing the potential negative impact of the bridge construction project.